Stunting Free Children Application to Improve Kindergarten Teachers Knowledge and Attitudes About Stunting - Dianna, Dianna; Damayanti, Dini Fitri (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2023)
The implementation of stunting detection can be done by providing health education information through information technology in the form of smartphones using an android-based application, namely the Stunting-Free Children (SFC) Application containing information about stunting and guidelines in detecting growth in children. The aim is to analyze the effect of SFC application on kindergarten teachers' knowledge and attitudes about stunting. This study used pseudo-experiments, with a form of pre-posttest with a control design. The sample of the study was 80 kindergarten teachers in Luewigoong District. Divided into 2 groups (intervention group using SFC application and control group using leaflet media). Sampling based on probability sampling techniques by simple random sampling. Statistical testing using the Chi Square and the average difference tests of two unpaired groups (Wilxocon test). The results showed that the effect of the application of SFC application on increasing knowledge by 22.7 (p < 0.05) with RR 1.5 (CI 95%) means that the SFC application can increase kindergarten teachers' knowledge about stunting. There was no effect of the application of SFC application on improving kindergarten teachers' attitudes about stunting (p>0.05). Recommendations for routine use of the SFC application by teachers in order to detect stunting events early